Enrichment of Vitamin E from crude palm oil by adsorption-desorption process - Phoon, Kah Yee; Ng, Hui Suan; Mokhtar, Mohd Noriznan; Zakaria, R.; Yim, Hip Seng (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Palm oil is unique compared to other vegetable oils due to it comprises of mixture of tocopherols and tocotrienols, also known as Vitamin E. In adsorption process, silica gel and Diaion HP 20 were employed to adsorb crude palm oil (CPO). Then, selective desorption process (modified Soxhlet extraction) was carried out to obtain two fractions using difference organic solvents. As a result, Vitamin E enriched oil was obtained when using Diaion HP 20 with methanol as solvent, giving up to 5.23 enrichment factor. Therefore, the proposed adsorption-desorption process has high potential to be applied for Vitamin E enrichment from CPO.